Association of three genetic loci with uric acid concentration and risk of gout: a genome-wide association study - Dehghan, Abbas; Köttgen, Anna; Yang, Qiong; Hwang, Shih-Jen; Kao, WH Linda; Rivadeneira, Fernando; Boerwinkle, Eric; Levy, Daniel; Hofman, Albert; Astor, Brad C; Benjamin, Emelia J; van Duijn, Cornelia M; et al. (The Lancet (British edition), 2008)
Hyperuricaemia, a highly heritable trait, is a key risk factor for gout. We aimed to identify novel genes associated with serum uric acid concentration and gout. Genome-wide association studies were done for serum uric acid in 7699 participants in the Framingham cohort and in 4148 participants in the Rotterdam cohort. Genome-wide significant single nucleotide polymorphisms (SNPs) were replicated in white (n=11 024) and black (n=3843) individuals who took part in the study of Atherosclerosis Risk in Communities (ARIC). The SNPs that reached genome-wide significant association with uric acid in either the Framingham cohort (p<5·0×10 −8) or the Rotterdam cohort (p<1·0×10 −7) were evaluated with gout. The results obtained in white participants were combined using meta-analysis. Three loci in the Framingham cohort and two in the Rotterdam cohort showed genome-wide association with uric acid. Top SNPs in each locus were: missense rs16890979 in SLC2A9 (p=7·0×10 −168 and 2·9×10 −18 for white and black participants, respectively); missense rs2231142 in ABCG2 (p=2·5×10 −60 and 9·8×10 −4), and rs1165205 in SLC17A3 (p=3·3×10 −26 and 0·33). All SNPs were direction-consistent with gout in white participants: rs16890979 (OR 0·59 per T allele, 95% CI 0·52–0·68, p=7·0×10 −14), rs2231142 (1·74, 1·51–1·99, p=3·3×10 −15), and rs1165205 (0·85, 0·77–0·94, p=0·002). In black participants of the ARIC study, rs2231142 was direction-consistent with gout (1·71, 1·06–2·77, p=0·028). An additive genetic risk score of high-risk alleles at the three loci showed graded associations with uric acid (272–351 μmol/L in the Framingham cohort, 269–386 μmol/L in the Rotterdam cohort, and 303–426 μmol/L in white participants of the ARIC study) and gout (frequency 2–13% in the Framingham cohort, 2–8% in the Rotterdam cohort, and 1–18% in white participants in the ARIC study). We identified three genetic loci associated with uric acid concentration and gout. A score based on genes with a putative role in renal urate handling showed a substantial risk for gout. Netherlands Organisation for Scientific Research (NWO); the National Heart, Lung, and Blood Institute.